2017
DOI: 10.3389/fnsys.2017.00065
|View full text |Cite
|
Sign up to set email alerts
|

HDAC3 Inhibitor RGFP966 Modulates Neuronal Memory for Vocal Communication Signals in a Songbird Model

Abstract: Epigenetic mechanisms that modify chromatin conformation have recently been under investigation for their contributions to learning and the formation of memory. For example, the role of enzymes involved in histone acetylation are studied in the formation of long-lasting memories because memory consolidation requires gene expression events that are facilitated by an open state of chromatin. We recently proposed that epigenetic events may control the entry of specific sensory features into long-term memory by en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 62 publications
(152 reference statements)
4
24
0
Order By: Relevance
“…However, a limitation of our approach is that we used only one dose of RGFP966. Several previous studies have found that systemic administration of 10 mg/kg of RGFP966 promotes memory and plasticity (Bieszczad, et al 2015; Malvaez et al 2013; Phan et al 2017). Malvaez et al (2013) found that a lower dose (3 mg/kg) enhanced object memory relative to vehicle but this effect was smaller compared to 10 mg/kg and 30 mg/kg of RGFP966.…”
Section: Discussionmentioning
confidence: 99%
“…However, a limitation of our approach is that we used only one dose of RGFP966. Several previous studies have found that systemic administration of 10 mg/kg of RGFP966 promotes memory and plasticity (Bieszczad, et al 2015; Malvaez et al 2013; Phan et al 2017). Malvaez et al (2013) found that a lower dose (3 mg/kg) enhanced object memory relative to vehicle but this effect was smaller compared to 10 mg/kg and 30 mg/kg of RGFP966.…”
Section: Discussionmentioning
confidence: 99%
“…The role of histone modifications has also been studied in this context. Pharmacological inhibition of histone deacetylases (HDAC) in Zebra Finches contributed to the memorization of conspecific vocalizations (Phan et al 2017). The fact that HDAC can be recruited by DNA methylation, which leads to the removal of acetyl groups resulting in constricted access to chromatin and transcriptional silencing (Day and Sweatt 2011), might indicate that DNA methylation regulates song memory formation in birds through the modulation of the structure of chromatin.…”
Section: Avian Learning and Memorymentioning
confidence: 99%
“…This discovery was followed by similar evidence in other songbird species, including two species of sparrow, Zonotrichia spp., and the canary, Serinus canarius [9]. Not surprisingly, these discoveries began an active field of research on lateralization of bird song at the behavioural, anatomical and cellular levels (see [10] for a recent study) and parallels have been drawn between acquisition of bird song and of human speech [11]. However, we mention this only in passing since, in this paper, we focus on lateralization of visual perception and response to visual stimuli.…”
Section: Studies Of Lateralization Conducted In Laboratory Settingsmentioning
confidence: 99%